Biosimilar drug lag and evolution in Malaysia: A retrospective analysis of regulatory approvals - Nguyen Thao My Hoang, Omotayo Fatokun, Muhammad Junaid Farrukh (Journal of Applied Pharmaceutical Science, 2025)
The availability of biosimilars has the potential to increase patient access to affordable biological treatments. However, a delay in national regulatory approval after global approval remains a concern, potentially impeding timely patient access. This study assessed the drug lag for biosimilars approved in Malaysia relative to the European Union (EU) and examined the evolution of biosimilar approvals in Malaysia between 4 August 2008 and 31 August 2023. The median biosimilar approval lag in Malaysia was 800 days (95% CI 398.57–1201.43). Over the study period, 18 INN biosimilars in 38 different brands were approved in Malaysia, with a majority (76.3%) of brand approvals occurring between 2016 and 2023. The number of brand approvals ranged from one to four per INN biosimilar, with a median of 2 (IQR = 1–3). The median time lag between the first and second biosimilar brand approvals was 608 days (IQR = 266–866), while that between the second and third brand approvals was 119.50 days (IQR = 50.25–1442.25). There was a notable drug lag for biosimilar approvals in Malaysia, but recent years showed an increasing trend in biosimilar brand approvals. Streamlined regulatory processes are essential to enhancing biosimilar availability and accessibility in Malaysia.
Keywords: Biosimilars, biological products, drug lag, Malaysia, regulatory approval, patient access